2018
DOI: 10.5334/joc.22
|View full text |Cite
|
Sign up to set email alerts
|

Number and Continuous Magnitude Processing Depends on Task Goals and Numerosity Ratio

Abstract: A large body of evidence shows that when comparing non-symbolic numerosities, performance is influenced by irrelevant continuous magnitudes, such as total surface area, density, etc. In the current work, we ask whether the weights given to numerosity and continuous magnitudes are modulated by top-down and bottom-up factors. With that aim in mind, we asked adult participants to compare two groups of dots. To manipulate task demands, participants reported after every trial either (1) how accurate their response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
3
13
0
1
Order By: Relevance
“…In terms of sensory integration theory, this finding can be interpreted as an increase in weights given to the continuous magnitudes. Thus, our results add to the growing body of evidence suggesting that these weights are dynamic and applied in an adaptive and flexible way (Leibovich et al, 2015, 2017; Leibovich, Kallai, & Itamar, 2016; Leibovich-Raveh et al, 2018). As mentioned before, different instructions, task difficulty, exposure duration, and task context can alter the effect of continuous magnitudes on dot comparison performance.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In terms of sensory integration theory, this finding can be interpreted as an increase in weights given to the continuous magnitudes. Thus, our results add to the growing body of evidence suggesting that these weights are dynamic and applied in an adaptive and flexible way (Leibovich et al, 2015, 2017; Leibovich, Kallai, & Itamar, 2016; Leibovich-Raveh et al, 2018). As mentioned before, different instructions, task difficulty, exposure duration, and task context can alter the effect of continuous magnitudes on dot comparison performance.…”
Section: Discussionsupporting
confidence: 67%
“…Further studies, which address the role of continuous magnitudes on numerosity processing, may add to our understanding about the interplay between discrete numerosity and continuous sensory cues. For example, it has been shown that the effect of continuous magnitudes on dot comparison performance can be altered by changes in instructions, task difficulty, stimulus duration, and task context (Leibovich et al, 2015; Leibovich-Raveh et al, 2018). Thus, the weights that are given to continuous magnitudes are not static but seem to depend on various experimental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study took this question one step forward by not only asking whether non-numerical magnitudes influence performance or not, but showing that (1) this influence, in an untrained animal, is moderated by the number of non-numerical magnitudes positively correlated with numerical quantity, and (2), that the number of non-numerical magnitudes, not their identity, influence performance. Since this is the first attempt to ask these questions in an untrained animal, and since it is well-known that the way the stimuli are built can greatly impact performance e.g., 32 , 36 , replication studies with the same and different stimuli that were composed in different ways are necessary to confirm or restrict the results and conclusions of the current study. We hope that this work will inspire similar research with different animals and different types of stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it also allows expanding the context of the task. Namely, magnitude discrimination, at least in humans, is context-dependent e.g., 32 , 33 . Given the multiple tasks magnitude discrimination may be required for (hunting, mate selection, avoiding predators, shelter-seeking), it is possible that for different tasks, different magnitudes will guide an animal’s decision.…”
Section: Discussionmentioning
confidence: 99%